2018
DOI: 10.1098/rsos.171809
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of nano-zinc to alleviate salinity stress on cotton plants

Abstract: To investigate the effect of nano-zinc fertilizer on growth, yield and mineral status of cotton plants grown under salt stress, a pot experiment was set up in the greenhouse of the National Research Centre. The treatments were as follows: (I) diluted seawater: 10% (S1), 20% (S2) and tap water as a control (S0), (II) 100 ppm (NZn1), 200 ppm (NZn2) nano-zinc and distilled water as a control (NZn0). Irrigation with 10 and 20% seawater decreased dry weight (DW) of leaves by 11.53 and 43.22%, while decreases in bol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(51 citation statements)
references
References 21 publications
4
43
0
Order By: Relevance
“…Nano-fertilizers applications are a potential solution to these problems. Application of nano-fertilizers represents one of the most appropriate strategies for achieving increased resource use efficiency, crop production, and reduced environmental contamination (Haripriya et al 2018;Hussein and Abou-Baker 2018;Bala et al 2019). Potent, non-toxic, highly stabile, slow-release, high efficiency, biocompatible, environment-friendly, and low-cost nano-nutrients could substitute conventional fertilizers and represent a viable solution to meeting the needs of rising demand for agricultural products (Nair et al 2010;Bala et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nano-fertilizers applications are a potential solution to these problems. Application of nano-fertilizers represents one of the most appropriate strategies for achieving increased resource use efficiency, crop production, and reduced environmental contamination (Haripriya et al 2018;Hussein and Abou-Baker 2018;Bala et al 2019). Potent, non-toxic, highly stabile, slow-release, high efficiency, biocompatible, environment-friendly, and low-cost nano-nutrients could substitute conventional fertilizers and represent a viable solution to meeting the needs of rising demand for agricultural products (Nair et al 2010;Bala et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Smaller particle size results in an increased concentration of particles of applied zinc and also increases the specific surface area of the fertilizer for use by the plant, which increases the dissolution rate of fertilizers with low solubility in water, like Zinc oxide. Earlier studies have already documented both the positive and negative impacts on physio-biochemical processes of several plants (Hussein and Abou-Baker 2018;Bala et al 2019). However, limited work has been done to evaluate the role of ZNP in regulating physiological and biochemical processes in response to salinity.…”
Section: Introductionmentioning
confidence: 99%
“…Excavating elite alleles that can Cotton yield decreases under salt stress. The previous studies reported that SBW, LP and BNPP remarkably decreased under salt stress [46][47][48]. In present study, we selected four different field soil salt environments with two year replicates to investigate the lint yield components of cotton accessions.…”
Section: Discussionmentioning
confidence: 97%
“…Cotton yield decreases under salt stress. Previous studies have reported that SBW, LP and BNPP are remarkably decreased under salt stress conditions [40][41][42]. In the present study, we selected four different field soil salt environments with two year replicates to investigate the lint yield components of cotton accessions.…”
Section: Discussionmentioning
confidence: 99%